Agroforestry—a key tool in the climate-smart agriculture context: a review on coconut cultivation in Sri Lanka - Dissanayaka, D. M. N. S.; Dissanayake, D. K. R. P. L.; Udumann, S. S.; Nuwarapaksha, T. D.; Atapattu, Anjana J. (Frontiers in Agronomy, 2023)
Long-term monoculture of coconuts has resulted in several land-use-related concerns, such as decreasing land productivity, degraded soil, and ineffective resource utilization on a local and global level. Modifying traditional coconut farming with agroforestry concepts is a well-suited predominant nature-based solution for Sri Lanka as well as for other coconut-growing countries to achieve environmental, social, and economic benefits. By intentionally and intensively integrating annual and perennial plants with farm animals in a dynamic and interactive manner, this land-use system creates a sustainable harmonious mini-ecosystem with landscape restoration. Agroforestry mixed coconut cultivation decreases the risk of crop failure, generates additional income sources, and balances the ecosystem functions by increasing species richness, enhancing soil physical, biological, and chemical properties, opening new carbon sequestration pathways, purifying air, and water sources, and being an excellent feedstock source for bioenergy generation. This environmentally friendly farming will promote the Kyoto Protocol and lessen global warming by limiting the atmospheric buildup of greenhouse gases. A proper and accurate plan is required to implement a successful and profitable long-lived coconut-based agroforestry system. The objective of this paper is to recognize the various agroforestry concepts applicable to coconut-based farming, highlight the wide range of benefits and ecosystem services that can be gained through in-situ and ex-situ agroforestry practices, and explore the challenges that may arise during the integration of agroforestry techniques into a coconut-based farming system.